2021
DOI: 10.3390/ma14195777
|View full text |Cite
|
Sign up to set email alerts
|

Waste Mineral Wool and Its Opportunities—A Review

Abstract: Massive waste rock wool was generated globally and it caused substantial environmental issues such as landfill and leaching. However, reviews on the recyclability of waste rock wool are scarce. Therefore, this study presents an in-depth review of the characterization and potential usability of waste rock wool. Waste rock wool can be characterized based on its physical properties, chemical composition, and types of contaminants. The review showed that waste rock wool from the manufacturing process is more worka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 130 publications
0
16
0
Order By: Relevance
“…However, there was no statistical difference between the UC and FC groups in terms of internal bond strength. It has been reported that in particleboards produced by adding 10, 20, and 30% stone wool using urea formaldehyde glue, the mineral wool reduced the bending strength by up to 65% and the internal bond strength by up to 71%, due to the reduction of the cohesion force inside the board (Mamiński et al 2011;Yap et al 2021). Cong et al (2021) added a layer of mineral wool and glass wool to epoxy-based carbon fiber polymeric laminates and investigated their combustion and mechanical properties.…”
Section: Mechanical and Physical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there was no statistical difference between the UC and FC groups in terms of internal bond strength. It has been reported that in particleboards produced by adding 10, 20, and 30% stone wool using urea formaldehyde glue, the mineral wool reduced the bending strength by up to 65% and the internal bond strength by up to 71%, due to the reduction of the cohesion force inside the board (Mamiński et al 2011;Yap et al 2021). Cong et al (2021) added a layer of mineral wool and glass wool to epoxy-based carbon fiber polymeric laminates and investigated their combustion and mechanical properties.…”
Section: Mechanical and Physical Propertiesmentioning
confidence: 99%
“…According to their results, depending on the increase in mineral wool, the mechanical properties and thermal conductivity values decreased and the thickness swelling increased. Existing studies have generally shown a reasonable increase in the ignition and combustion resistance of wood-based composite materials mixed with stone wool fillers; however, the deterioration of mechanical properties cannot be disregarded for woodpolypropylene composites (Yap et al 2021). Recently, the interest in and demand for environmentally friendly engineered wood-based products has been increasing as a result of the energy crisis and health concerns.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, sound absorbers have poor mechanical stability [41]. Thus, numerous research studies have emphasized finding the balance between mechanical strength and sound absorption [42,43].…”
Section: Measurement Parametersmentioning
confidence: 99%
“…However, recycling of sheep wool fibers and use as a construction material after minor treatment has been investigated, as these fibers have a high elastic modulus of up to 4 GPa [ 4 ]. In addition, sheep wool has increased strength due to chemical interaction between the protein components [ 23 ].…”
Section: Introductionmentioning
confidence: 99%